Hoysala architecture; Somanathapura, Keshava temple, Outer wall of the southern garbhagriha, Varaha (bore) avatara of Lord Vishnu - Lawrence Rodrigues (2021)
Image courtesy: Lawrence Rodrigues - www.yatrikaone.com